1992
DOI: 10.1007/bf01836073
|View full text |Cite
|
Sign up to set email alerts
|

A case of congenital leukemia with monosomy 7

Abstract: A case of congenital leukemia with monosomy 7 is reported. Immunological study of the blast cells using monoclonal antibodies was suggestive of both myelomegakaryocytic and T-lymphoblastic leukemia. Chromosomal analysis of the bone marrow cells showed monosomy 7. Chemotherapy was initiated with a combination of adriamycin, cytosine arabinoside, 6-mercaptopurine, and prednisolone. The patient obtained complete remission, which has been maintained for 4 years and 1 month. He receives no chemotherapy now. Our cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Interestingly, four patients with congenital leukaemia have been described in the literature who showed a phenotypic switch from lymphoid to myeloid leukaemia (Hayashi et al, 1985;Ridge et al, 1995;Brissette et al, 1996) or vice versa (Shimizu et al, 1989) at relapse. In another four patients both myeloid and lymphoid surface markers (biphenotypic) were found on the blasts (Rechavi et al, 1988;Fugazza et al, 1992;Shitara et al, 1992;Matamoros et al, 1994) (Table II). It is assumed that these leukaemias develop from an early stem cell that can differentiate in both the myeloid and the lymphoid direction.…”
Section: Differentiation From Tmdmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, four patients with congenital leukaemia have been described in the literature who showed a phenotypic switch from lymphoid to myeloid leukaemia (Hayashi et al, 1985;Ridge et al, 1995;Brissette et al, 1996) or vice versa (Shimizu et al, 1989) at relapse. In another four patients both myeloid and lymphoid surface markers (biphenotypic) were found on the blasts (Rechavi et al, 1988;Fugazza et al, 1992;Shitara et al, 1992;Matamoros et al, 1994) (Table II). It is assumed that these leukaemias develop from an early stem cell that can differentiate in both the myeloid and the lymphoid direction.…”
Section: Differentiation From Tmdmentioning
confidence: 99%
“…A Medline search for English language papers on congenital and neonatal leukaemia between 1975 and 2000 was carried out. A total of 102 patients with congenital leukaemia, as defined by the diagnostic criteria stated above, were identified (Abe et al , 1983; Allan et al , 1989; Badhe & Sane, 1992; Bastard et al , 1985; Benedict et al , 1979; Bernstein et al , 1984; Bernstein et al , 1987; Brissette et al , 1996; Campbell et al , 1997; Carney et al , 1992; Chu et al , 1983; Clark et al , 1984; Dinulos et al , 1997; Djernes et al , 1976; Embon et al , 1995; Fernandez et al , 1999; Francis et al , 1989; Fugazza et al , 1992; Gale & Toledano, 1984; Gale et al , 1986; Garewal et al , 1993; Gilgenkrantz et al , 1983; Gottesfeld et al , 1989; Gray et al , 1986; Hagemeijer et al , 1981; Hanada et al , 1991; Hara et al , 1984; Hayashi et al , 1985; Hazani et al , 1993; Heikinheimo et al , 1994; Huret et al , 1993; Irwin & Campbell, 1978; Isaacs, 1987; Jadhav et al , 1988; Kojima et al , 1989; Kurosawa et al , 1987; Kushwaha et al , 1977; Lampkin et al , 1985; Las‐Heras et al , 1986; Lasson & Goos, 1981; Liang et al , 1986; Liang et al , 1993; Lilleyman, 1980; Matamoros et al , 1994; Mayer et al , 1995; McCoy et al , 1995; Monpoux et al , 1996; Mori et al , 1997; Muchi et al , 1985; Odom & Gordon, 1984; Ohyashiki et al , 1988; Raney et al , 1979; Rechavi et al , 1988; Resnik & Brod, 1993; Ridge et al , 1995; Sainati et al , 1996; Sait et al , 1988; Seo et al , 1986; Shah et al , 1984; Shimizu et al , 1987; Shimizu et al , 1989; Shitara et al , 1992; Silberstein et al , 1979; Simon et al , 1984; Sippe, 1981; Spier et al ...…”
Section: Review Of the Literature (Including The Dutch Patients) (Tabmentioning
confidence: 99%
“…In addition, monosomy of chromosome 7 has been documented in cases of AML M7 with or without Down's syndrome. 227,248,249 Conversely, cases with aberrations of chromosome 5 more often expressed T cell-related antigens such as CD2 or CD7. 170 An Italian study on adult AML showed that TdT pos CD7 pos immunophenotype correlated with chromosome 5 and/or 7 aberrations and with the multiple-drug resistance phenotype.…”
Section: Monosomies and Deletions In Chromosomes 5 And 7 In Amlmentioning
confidence: 99%